2003
DOI: 10.1210/en.2003-0403
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Steroidogenesis, Defective Reproductive Organs, and Infertility in Transgenic Male Mice Overexpressing Human Chorionic Gonadotropin

Abstract: We previously developed a transgenic (TG) mouse model that overexpresses the human chorionic gonadotropin (hCG) beta-subunit under the universal human ubiquitin C promoter, displaying in males a modest 3-fold increase in circulating levels of LH/hCG bioactivity. The males were fertile and presented with a mild reproductive phenotype. To achieve higher levels of hCG, a double TG model was generated by cross-breeding the hCG beta-expressing mice with another TG line harboring a ubiquitin C/common alpha-subunit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 50 publications
6
102
0
Order By: Relevance
“…associated with a demyelinating peripheral neuropathy (30,31). Transgenic mice that overexpress human chorionic gonadotropin develop functional urethral obstruction that is associated with enlargement of prostates and seminal vesicles (32). None of the defects that are observed in these mice is similar to the mgbϪ/Ϫ phenotype, suggesting that the mgbϪ/Ϫ mouse is a unique transgenic model.…”
Section: Discussionmentioning
confidence: 99%
“…associated with a demyelinating peripheral neuropathy (30,31). Transgenic mice that overexpress human chorionic gonadotropin develop functional urethral obstruction that is associated with enlargement of prostates and seminal vesicles (32). None of the defects that are observed in these mice is similar to the mgbϪ/Ϫ phenotype, suggesting that the mgbϪ/Ϫ mouse is a unique transgenic model.…”
Section: Discussionmentioning
confidence: 99%
“…In the hCGβ TG mice (hCGβ+), the hCGβ transgene is expressed also in the pituitary cells expressing the endogenous common α-subunit. This enables dimerization of the TG and endogenous subunits to form biologically active hCG (human β/mouse α-subunit), inducing 3-4 fold elevation in hCG/LH bioactivity in males, but 30-fold increase in females compared to wild-type (WT) littermates (Rulli et al, 2002;Rulli et al, 2003). Phenotypic characterization of the hCGβ+ males revealed no obvious alterations, with the exception of slightly decreased testis weights most probably due to decreased FSH-levels seen in these males .…”
Section: Hcg Overexpressing Transgenic Micementioning
confidence: 99%
“…Transgenic (TG) mice overexpressing hCGβ and common α-subunits under the human ubiquitin C promoter were produced by conventional pronuclear injection techniques (Rulli et al, 2002;Rulli et al, 2003). In these mice, the ubiquitin C promoter maintains low level TG expression in most tissue types, and its activity has been shown to start on embryonic day 10.5 (Schorpp et al, 1996).…”
Section: Hcg Overexpressing Transgenic Micementioning
confidence: 99%
“…In mouse models of ectopic overexpression of hCG producing very high levels of testosterone, infertility and Leydig cell hyperplasia were observed in older animals (Rulli et al, 2002;Matzuk et al, 2003;Rulli et al, 2003). Futher studies showed that although there was a significant increase in testosterone levels in hCG expressing mice as early as postnatal day 5, there was no evidence of early puberty (Ahtiainen et al, 2005).…”
Section: Phenotype Of the Yhr Transgenic Micementioning
confidence: 99%
“…Consequently, genetically modified mouse models with loss-offunction and gain-of-function phenotypes have been generated to elucidate the molecular mechanisms of gonadotropin action in vivo (Risma et al, 1995;Kumar et al, 1997;Dierich et al, 1998;Kumar et al, 1998;Lei et al, 2001;Zhang et al, 2001;Rulli et al, 2002;Matzuk et al, 2003;Rulli et al, 2003;Ma et al, 2004). Of all the human mutations that are known for gonadotropins and their receptors, the most reported are the activating and inactivating LHR mutations.…”
Section: Introductionmentioning
confidence: 99%